2021
DOI: 10.1016/j.nbd.2020.105189
|View full text |Cite
|
Sign up to set email alerts
|

Lateral habenula dysfunctions in Tm4sf2−/y mice model for neurodevelopmental disorder

Abstract: Mutations in the TM4SF2 gene, which encodes TSPAN7, cause a severe form of intellectual disability (ID) often comorbid with autism spectrum disorder (ASD). Recently, we found that TM4SF2 loss in mice affects cognition. Here, we report that Tm4sf2 −/y mice, beyond an ID-like phenotype, display altered sociability, increased repetitive behaviors, anhedonic- and depressive-like states. Cognition relies on the integration of information from several brain areas. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Previous reports revealed that integrins are involved in signal transduction by interacting with TSPANs (Bassani & Cingolani, 2012; Hemler, 2005; Yanez‐Mo et al, 2009). Specifically, TSPAN7 influences actin remodeling by forming complexes with β1 integrin, PICK1, and AMPAR in hippocampal neurons (Bassani et al, 2012), thus leading to the observed cognitive impairment in Tm4sf2 knockout mice (Murru et al, 2017, 2021). The results of the current study propose that TSPAN7 interacts with both β3 integrin and RANK in osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports revealed that integrins are involved in signal transduction by interacting with TSPANs (Bassani & Cingolani, 2012; Hemler, 2005; Yanez‐Mo et al, 2009). Specifically, TSPAN7 influences actin remodeling by forming complexes with β1 integrin, PICK1, and AMPAR in hippocampal neurons (Bassani et al, 2012), thus leading to the observed cognitive impairment in Tm4sf2 knockout mice (Murru et al, 2017, 2021). The results of the current study propose that TSPAN7 interacts with both β3 integrin and RANK in osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that TSPAN7 was involved in spine maturation in cultured hippocampal neurons through a direct interaction with PICK1 ( Bassani et al, 2012 ). Tspan7 knockout caused an ASD-related phenotype in mice, and the deletion of TSPAN7 altered voltage-gated ion channels function and decreased PKC-ERK signaling ( Murru et al, 2021 ). Synaptic dysfunction had been revealed to be a hallmark of ASD ( Guang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced body weight and ad libitum plasma glucose was observed in Tspan7 y/− mice (Figure 2a,b), but this was not linked to changes in plasma insulin (measured as insulin and C‐peptide, Figure 2c,d). These effects may instead be attributable to the neurological manifestations of Tspan7 ablation, including depressive behaviour 23 . We observed no change in circulating proinsulin levels (Figure 2e), suggesting normal insulin processing in Tspan7 y/− β‐cells.…”
Section: Resultsmentioning
confidence: 77%